TRADISI MA’NENE PADA MASYARAKAT SUKU TORAJA KECAMATAN MAKALE KABUPATEN TANA TORAJA - Sisilia Christiani Octavia Oroh (HOLISTIK, Journal of Social and Culture, 2023)
The Ma'Nene tradition in the Toraja tribe in Makale District, which has undergone changes in its procedures and implementation, which was previously in the Aluk Todolo version, has now undergone changes in the Christian version. Ma'Nene is a memorial service for the family of the deceased as a form of gratitude and appreciation to the deceased for his services to the descendants who have been left behind by lifting the corpse from the burrow (grave) and lining the clothes or wrapping the corpse with new cloth. The process of implementing Ma'Nene in a belief has almost similarities, but the rules of implementation are different, the function of the Ma'nene version of Aluk Todolo is to ask for blessings to the spirits of the ancestors, while the function of the Christian version of Ma'nene for Aluk Todolo and Christians has something in common, namely as a sign of affection and appreciation for the family of the deceased. So it is undeniable that the family or relatives of the deceased tried their best to carry out Ma'Nene so that they could obtain worldly salvation. The Ma'Nene tradition is an ancestral heritage that still survives today even though many have embraced the divine religion. The loyalty of the Torajan people to the trust of their ancestors is firmly embedded in the soul of every person. In Torajan society, if they have not carried out the Ma'Nene tradition, during their lives and until their descendants will not get salvation. Therefore, it is important for the Torajan people to carry out this Ma'Nene Tradition. Keywords : Tradition, Ma'Nene, Toraja